2016
DOI: 10.1002/jemt.22729
|View full text |Cite
|
Sign up to set email alerts
|

Surface ultrastructure of gills in relation to the feeding ecology of an angler catfishChaca chaca(Siluriformes, Chacidae)

Abstract: Surface ultrastructure of the gills of the angler catfish Chaca chaca was investigated to unravel the adaptive modifications associated with the feeding ecology of the fish. The fish is often found in mud or in soft substrates where they remain buried both for protection and to feed. Gill rakers present on the gill arch in most fish species are absent in this fish. The absence of gill rakers are associated with the feeding habit of the fish and is considered to facilitate the swallowing of captured prey smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The main gill's functions are gas exchange in nearly all fishes, some waste products elimination, and the conservation of the fish's salt equilibrium (Perna & Fernandes, 1996). Today, the significance of structure and function of gills were studied in different fish species (M. Abumandour & El‐Bakary, 2017; M. Abumandour & Gewaily, 2016b; M. M. Abumandour, 2019; Alsafy, 2013; Hanafy, 2020; Mistri, Verma, Kumari, Mittal, & Mittal, 2016). Great variability in the structure of the gills thus demanding to study its morphology to provide information about its histophysiology in fishes in various environments (D. R. Eiras‐Stofella & Charvet‐Almeida, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The main gill's functions are gas exchange in nearly all fishes, some waste products elimination, and the conservation of the fish's salt equilibrium (Perna & Fernandes, 1996). Today, the significance of structure and function of gills were studied in different fish species (M. Abumandour & El‐Bakary, 2017; M. Abumandour & Gewaily, 2016b; M. M. Abumandour, 2019; Alsafy, 2013; Hanafy, 2020; Mistri, Verma, Kumari, Mittal, & Mittal, 2016). Great variability in the structure of the gills thus demanding to study its morphology to provide information about its histophysiology in fishes in various environments (D. R. Eiras‐Stofella & Charvet‐Almeida, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…While microridges have been extensively described in fish skin (Hawkes, 1974;Bereiter-Hahn et al, 1979;Fishelson, 1984;Arellano et al, 2004;Mistri et al, 2018), these structures are found in many other types of teleost tissue. Cornea (Collin and Collin, 1997, 2000, gills (Arellano et al, 2004;Eiras-stofella, 2000;Kumari et al, 2009;Mistri et al, 2016), nasal epithelium (Zeiske et al, 1994;Hansen and Zeiske, 1998), operculum (Mittal et al, 2004), head/ snout epidermis (Rai et al, 2012), and oral mucosa (Uehara et al, 1988(Uehara et al, , 1990Kumari et al, 2005) have all been shown to have microridges protruding from outer surfaces of the superficial layer. Microridges have also been identified in the epithelial enveloping layer (EVL) of gastrulating zebrafish (Danio rerio) embryos (Zalik et al, 1999;Crawford et al, 2003), on the surface of unfertilized Brachydanio eggs (Hart and Donovan, 1983), and in superficial epithelium of embryonic Poeciliopsis (Panhuis et al, 2017).…”
mentioning
confidence: 99%
“…The most characteristic feature of the European barracuda gills is the lacking the gill rakers. Also, Mistri, Verma, Kumari, Mittal, and Mittal (2016) observed the absence of the rakers in angler catfish chaca chaca and the lacking of these rakers permits smooth swallowing of the captured preys without any hindrance. Meanwhile, many authors recorded presence of gill rakers with a different appearance in a wide variety of fish with different feeding habits; The spaces between the gill rakers determine the size of the swallowed food items concerning the feeding habits of different fish species; the narrow spacing correlated to the small sized preys that will be eaten (Magnuson & Heitz, 1971;O'Brien, 1987).…”
Section: Discussionmentioning
confidence: 86%
“…The most characteristic feature of the European barracuda gills is the lacking the gill rakers. Also, Mistri, Verma, Kumari, Mittal, and Mittal (2016) observed the absence of the rakers in angler catfish chaca chaca and the lacking of these rakers permits smooth swallowing of the captured preys without any hindrance. Meanwhile, many authors recorded presence of gill rakers with a different appearance in a wide variety of fish with different feeding habits; Alsafy (2013) in sea bream and sea bass, Elsheikh (2013) in Oreochromis niloticus , Chrysichthys auratus , and Clarias gariepinus , Khalaf‐Allah, Azab, and Mohamed (2016) in Sparus aurata , Diplodus noct , Rhapdosargus haffara , and Boops boops , Abumandour and El‐Bakary (2017) in grey gurnard fish and striped mullet fish, Märss, Wilson, Saat, and Špilev (2017) in European plaice, European flounder, and turbot and Hanafy (2020) in European hake, Bassuoni (2021) in Bagrus bayad.…”
Section: Discussionmentioning
confidence: 99%